2021
DOI: 10.1088/1755-1315/852/1/012039
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Adsorption of Heavy Metal Ions from Model Solutions by Humic Acids Isolated from Sapropel

Abstract: The article presents the results of research on adsorption of Cu2+, Ni2+ and Pb2+ ions from model solutions with concentrations of 2–25 mg/dm3 under static conditions using humic acids isolated from the sapropel of Lake Lipovo, Novgorod region as an adsorbent. Adsorption equilibrium in the model solution-adsorbent systems occurs in 2 hours. The kinetic curves of adsorption of Cu2+, Ni2+ and Pb2+ ions from model solutions by humic acids are described with a pseudo-second order kinetic model; consequently, the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In the reports where they used WLW, adsorption capacities of 0.2899 [40] and 39.6 mg/g [71] were obtained. In terms of what has been reported in the literature for Cu(II) adsorption using adsorbents such as Zn-Cl2-activated carbon [64], chitosan [34], DCDP [34], sapropel humic acids [58], almond [39], peanut shell [37], charred bones, and bentonite [52], the reported adsorption capacities were between 6.07 and 195.88 mg/g. When comparing the adsorption capacities of WLW and carbonized water lily as adsorbents, the latter had a slightly higher adsorption capacity of 24.3 mg/g [73], compared to WLW with an adsorption capacity of 23 mg/g [67].…”
Section: Kinetic Mechanism Of Ni(ii) and Cu(ii) Adsorptionmentioning
confidence: 69%
See 3 more Smart Citations
“…In the reports where they used WLW, adsorption capacities of 0.2899 [40] and 39.6 mg/g [71] were obtained. In terms of what has been reported in the literature for Cu(II) adsorption using adsorbents such as Zn-Cl2-activated carbon [64], chitosan [34], DCDP [34], sapropel humic acids [58], almond [39], peanut shell [37], charred bones, and bentonite [52], the reported adsorption capacities were between 6.07 and 195.88 mg/g. When comparing the adsorption capacities of WLW and carbonized water lily as adsorbents, the latter had a slightly higher adsorption capacity of 24.3 mg/g [73], compared to WLW with an adsorption capacity of 23 mg/g [67].…”
Section: Kinetic Mechanism Of Ni(ii) and Cu(ii) Adsorptionmentioning
confidence: 69%
“…In other studies that have used different adsorbents, the adsorption capacity has been found to be between 0.256 and 190.38 mg/g using CoFeO 2 /SO 2 nanoparticles [54], magnetized graphene [56], magnetite-bentonite nanocomposites [57], sapropel humic acids [58], calcium carbonate in bacterial magnetosomes [36], hydroxyapatite [59], lemon peel [60], bamboo modified with mercaptoacetic acid and carbon disulfide [61], wheat and rice biochar [46], charred bones [62], and charcoal [63]. ©.…”
Section: Ni(ii) and Cu(ii) Adsorption Isotherms Using Wlw And Wlnmentioning
confidence: 99%
See 2 more Smart Citations